Conventions in the XXth Century Drame (Augustus Strindberg and Eugene O’Neill) - Baužytė, Galina (Literatūra, 1972)
The problem of dramatic conventions must be solved in close relationship with the conventional nature of art in general and the peculiarities of the dramatic genre in particular. The problem has been widely discussed by such western critics as John Gassner, Francis Fergusson and Siegfried Melchinger. The interest of Soviet literary criticism in the problem of dramatic conventions is manifested in numerous collections of critical essays such as "Modern Drama Abroad" (1962), "Expressionism" (1966), "Modern Theatre Abroad" (1969) etc. The article discusses only certain aspects of conventions in the XXth century drama, namely those connected with the playwright’s aim to present the phenomena of the spiritual sphere and to express the conscious and the subconscious. The problem is analysed on the basis of Strindberg’s dream plays and O’Neill’s experimental dramas. In the introduction some general reference is made to the relation between dramatic images and life. Strindberg’s drama "A Dream Play" is subject of special analysis. The symbolic images as well as the disconnected episodes of the play reveal the illogic of dreams. Instantaneous transformations of personages and objects convey the transition from one spiritual state to another. The style and the structure of "A Dream Play" (which are also manifest in the trilogy "To Damascus" and "The Ghost Sonata") were elaborated by the authors of the expressionist and the surrealist drama. Augustus Strindberg exerted a great influence on Eugene O’Neill. The tragic conception of life and an interest in the conscious and the subconscious are common to both playwrights. The conventions in "The Emperor Jones" (1920) and in "The Hairy Ape" (1922) are based on the playwright’s aim to present the state of mind of a man who has lost his harmony with nature and is obsessed by complexes of guilt and inferiority. The reality of life is presented through the disordered mind of the hero. In "The Great God Brown" (1926) and "Days Without End" (1934) the disharmony and the dualism of a personality are revealed by means of masks and an "alter ego". In "Strange Interlude" the playwright uses "asides" (the characters speaking their thoughts) which to some extent correspond to the stream of consciousness in the novel. The conventions in Strindberg’s dream plays and O’Neill’s dramas demonstrate their aim to explore the complex spiritual world of contemporary man and to launch a new dramatic form for it. Both playwrights considered the limits of the traditional drama insufficient and thus tried to widen them.